Comparison of preservation and transportation protocols for preloaded Descemet membrane endothelial keratoplasty - Romano, Vito (Br J Ophthalmol, 2018)
BACKGROUND/AIMS: Descemet membrane endothelial keratoplasty (DMEK) preparation is technically demanding and is a limiting factor for uptake of this kind of surgery. Supply methods that simplify the procedure for surgeons are key to increasing uptake. This study compares two different shipping protocols for DMEK. METHODS: An 8.5 mm DMEK graft was punched, marked and loaded for transportation in two different conditions: (A) endothelium trifolded inwards in organ culture conditions (n=7) and (B) endothelium rolled outwards in hypothermic conditions (n=7). Tissues were shipped from Italy to the UK, then analysed for orientation, endothelial cell density, denuded areas, cell mortality, triple viability staining (Hoechst/ethidium homodimer/calcein AM (HEC)), immunolocalisation of ZO-1 and Na/K-ATPase proteins, visualisation of actin filaments using phalloidin and histological analysis using H&E on paraffin-embedded sections. RESULTS: All tissues clearly showed the mark used for graft orientation. After shipping in condition A, there was an increase in cell mortality of 8.1% and in denuded areas of 22.4%, whereas for condition B there was an increase in cell mortality of 14.2% and in denuded areas of 34.3% after shipping. HEC staining revealed areas of viable cells and apoptotic cells, with large denuded areas found in the periphery for condition B and within folds for condition A. CONCLUSIONS: Prestripped preloaded DMEK grafts retained sufficient viable cells for transplantation, with condition A (endothelium-in) offering the advantage of greater flexibility of use due to a longer shelf-life. HEC analysis provides further detailed information as to the status of DMEK grafts and should be used in future similar studies.